Cutting Force of End Milling Carbon Fibre Reinforced Polymer On Different Tool Geometries and Fibre Orientations: A Review: A Review - Ong, Wei Ming; Bin Abd Rahim , Erween (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In the recent years, Carbon Fibre Reinforced Polymer (CFRP) involves in a wide range of industrial applications due to the improved functional performance resulting from its superb mechanical properties. Due to the highly nonlinear, inhomogeneous, and abrasive character of CFRP composite, post machining is currently regarded an exceedingly unfavourable operation to ensure that the manufactured components fulfil their dimensional tolerances, surface quality, and other functional criteria. In this research, a complete analysis of the literature is provided with a focus on the influence of tool geometries and fibre orientations on cutting force in the end milling of CFRP composite. The results of this review study are considered to be reliable as the past studies used are those being filtered with key search terms and identical study outcome. In the milling of CFRP composite at constant spindle speed and feed rate, the cutting force decreases with increasing number of flutes of the cutting tool. A negative relationship is observed between the rake angle of cutting tool and the machining force during milling CFRP under constant relief angle, cutting speed, depth of cut and direction of cut. In the milling of CFRP under constant rake angle, helix angle, cutting speed and feed rate, the radial force and tangential force are found to be the greatest on CFRP with fibre orientation of 0⸰ and 135⸰ respectively. Whereas, CFRP with fibre orientation of 45⸰ recorded the smallest value for both cutting force components.